A technique of inculcating technological culture among masters of production training in the agrarian sphere under the conditions of the regional methodological service center - Shamraliuk, O. (Problems of Engineer-Pedagogical Education, 2019)
The article presents a study on designing a technique for the development of the technological culture of the masters of production training of the agrarian profile in the educational (scientific) and methodological centers of vocational education. The methodological basis of the developed technique is the concept of lifelong learning, the strategy of pedagogical interaction, the competence paradigm, andragogic, axiological, culturological, technological and personal-activity research approaches. The suggested technique determines the stages, forms of interaction between subjects of the educational process, as well as the content, methods and means of developing the technological culture of the masters of production training of the agrarian profile. The structural components of the technique include motivational, practical and analytical stages. The content of the regional methodological work is modernized taking into account the achievements of modern pedagogical science and effective pedagogical practice, labor market requirements, state and regional target educational programs and program goals of vocational education institutions. A corresponding educational environment has been formed. The paper substantiates and justifies the use of project-based, problem-solving, game-based, interactive and case-study educational technologies. The results of the research prove that the application of mixed educational technologies allows pedagogues to work at an individual pace to improve the technological culture. The introduction of the suggested technique creates conditions for constructive changes in the development of the technological culture of the masters of production training of the agrarian profile.